Checklist of the Cerambycidae (Coleoptera: Chrysomeloidea) of Oaxaca, Mexico - Martínez-Hernández, José Guadalupe; Rös, Matthias; Pérez-Flores, Oscar; Toledo-Hernández, Víctor Hugo (Zootaxa, 2024)
The knowledge of the Cerambycidae (Coleoptera) family from the Mexican state of Oaxaca is updated based on specialized literature, databases, and specimens preserved in entomological collections. A total of 565 species (including subspecies) are recorded for the state. Leptostylus notaticollis Bates, 1880 is a new record for Mexico and 64 species, 28 genera, and four tribes are recorded for the first time for Oaxaca.